Respuesta :
If
[tex]y=\displaystyle\sum_{n=0}^\infty a_nx^n[/tex]
then
[tex]y'=\displaystyle\sum_{n=1}^\infty na_nx^{n-1}=\sum_{n=0}^\infty(n+1)a_{n+1}x^n[/tex]
The ODE in terms of these series is
[tex]\displaystyle\sum_{n=0}^\infty(n+1)a_{n+1}x^n+2\sum_{n=0}^\infty a_nx^n=0[/tex]
[tex]\displaystyle\sum_{n=0}^\infty\bigg(a_{n+1}+2a_n\bigg)x^n=0[/tex]
[tex]\implies\begin{cases}a_0=y(0)\\(n+1)a_{n+1}=-2a_n&\text{for }n\ge0\end{cases}[/tex]
We can solve the recurrence exactly by substitution:
[tex]a_{n+1}=-\dfrac2{n+1}a_n=\dfrac{2^2}{(n+1)n}a_{n-1}=-\dfrac{2^3}{(n+1)n(n-1)}a_{n-2}=\cdots=\dfrac{(-2)^{n+1}}{(n+1)!}a_0[/tex]
[tex]\implies a_n=\dfrac{(-2)^n}{n!}a_0[/tex]
So the ODE has solution
[tex]y(x)=\displaystyle a_0\sum_{n=0}^\infty\frac{(-2x)^n}{n!}[/tex]
which you may recognize as the power series of the exponential function. Then
[tex]\boxed{y(x)=a_0e^{-2x}}[/tex]
Solution of differential equation is, [tex]y=e^{-2x}+c[/tex]
Given differential equation is,
[tex]y'+2y=0\\\\\frac{dy}{dx}+2y=0[/tex]
Using separation of variable.
[tex]\frac{dy}{y}=-2dx[/tex]
Integrating both side.
[tex]ln(y)=--2x\\\\y=e^{-2x}+c[/tex]
Learn more:
https://brainly.com/question/1164377